2017
DOI: 10.1016/j.ymgmr.2017.01.003
|View full text |Cite
|
Sign up to set email alerts
|

A new variant in PHKA2 is associated with glycogen storage disease type IXa

Abstract: Glucogenosis type IX is caused by pathogenic variants of the PHKA2 gene. Herein, we report a patient with clinical symptoms compatible with Glycogen Storage Disease type IXa. PYGL, PHKA1, PHKA2, PHKB and PHKG2 genes were analyzed by Next Generation Sequencing (NGS). We identified the previously undescribed hemizygous missense variant NM_000292.2(PHKA2):c.1963G > A, p.(Glu655Lys) in PHKA2 exon 18. In silico analyses showed two possible pathogenic consequences: it affects a highly conserved amino acid and disrup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…The fact that megakaryocytes from MF BM contain high numbers of large, electron-dense glycosomes suggests that these cells store great levels of glycogen in its insoluble polyglucosan form that is not readily available for energy homeostasis. Further support for this hypothesis comes from a re-analyses of the expression signature of MF BM (33) that identified modest fold changes above threshold in the expression of several genes of the glycogen pathway, four of which (PHKA2, PHKB, and PYGL down-regulated whereas PRDM8 upregulated) mutated in inherited disorders associated with increased glycogen storage (38)(39)(40)(41)(42)(43)(44) (Table S2, Figure S3). Upregulation of PRDM8 expression is particularly intriguing because gain of function mutations of this gene are associated with the neurodegenerative Lafora disease (30,41) which is characterized by the presence in the neurons of specific polyglucosan-rich glycosomes, defined Lafora body, similar in morphology to some of the glycosomes identified by us in the malignant megakaryocytes from MF BM.…”
Section: Discussionmentioning
confidence: 96%
“…The fact that megakaryocytes from MF BM contain high numbers of large, electron-dense glycosomes suggests that these cells store great levels of glycogen in its insoluble polyglucosan form that is not readily available for energy homeostasis. Further support for this hypothesis comes from a re-analyses of the expression signature of MF BM (33) that identified modest fold changes above threshold in the expression of several genes of the glycogen pathway, four of which (PHKA2, PHKB, and PYGL down-regulated whereas PRDM8 upregulated) mutated in inherited disorders associated with increased glycogen storage (38)(39)(40)(41)(42)(43)(44) (Table S2, Figure S3). Upregulation of PRDM8 expression is particularly intriguing because gain of function mutations of this gene are associated with the neurodegenerative Lafora disease (30,41) which is characterized by the presence in the neurons of specific polyglucosan-rich glycosomes, defined Lafora body, similar in morphology to some of the glycosomes identified by us in the malignant megakaryocytes from MF BM.…”
Section: Discussionmentioning
confidence: 96%
“…There is a specific growth pattern that is found to be associated in males with X-linked GSD IX. Typically, these affected individuals are found to have a normal height at birth, followed by substantial growth retardation between the ages of 2 and 10 years of age, significantly delayed puberty, and then go on to attain normal adult parameters [ 12 ]. Our patient's height trended downwards since his evaluation at 15 months of age; he was at 37 percentile at 15 months, 10 percentile on 17 months visit, and only 5 percentile upon his last visit at 30 months of age.…”
Section: Discussionmentioning
confidence: 99%
“…Often no intervention is needed for growth delay; however, frequent monitoring will be needed in this patient in order to prevent long-term complications. Adverse effects including pubertal delay can in turn cause reduced bone density and increased risk of bone fractures in adulthood [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also shown that some untreated children may develop growth delay and psychological distress, and adult patients have an elevated risk of bone fracture. 3,4 Thus, to make a definitive and timely diagnosis of the GSD types or subtypes mainly depends on molecular genetic studies of the relevant genes.…”
Section: Introductionmentioning
confidence: 99%